TRACES OF CRITICAL SPIRITUAL PEDAGOGY IN INDONESIAN EFL TEACHERS' CHRISTIAN-BASED CLASSES - Puspita, Aurelia Melinda Herka; Mambu, Joseph Ernest (TEFLIN Journal, 2020)
The incorporation of critical pedagogical (CP) perspectives into ELT classrooms has been widely discussed in ELT literature, but how English language teachers in Indonesian schools integrate them in their lessons has not been sufficiently documented. This study aims to investigate to what extent CP perspectives are integrated within the learning process to teach four basic English skills, although the teachers were not familiar with CP. Two in-service English teachers from a private junior high school in Central Java, Indonesia, filled in a questionnaire designed to identify their pedagogical identity. They were also interviewed and observed to further investigate their responses in the questionnaire and to explore the realization of the CP practice. The data was classified based on the components of critical language pedagogy proposed by Crookes (2013). The results showed that as students' wholeness was acknowledged, the learning process integrated cultural and critical contents to teach a particular language feature. During the learning process, there was a great deal of the inclusion of spiritual values as a way of demonstrating the students' criticality.